Y Generations Financial Literacy Indexes In Indonesia - Aribawa, Dwitya (IJTB (International Journal of Technology And Business), 2017)
Financial literacy (FL) initiatives are known as becoming a key element for achieving financial reform around the world. This study aim to assess the degree of financial literacy using the basic and advance financial literacy index approach to measures financial literacy among young generations. In constructing financial literacy index, there are four steps: grouping questions, assigning score for each question, calculating weight for each question, and constructing financial literacy index. Primary data collected using online questionnaires through supervision by researcher. It is found that financial literacy among university students is vary differs depend on their background and willingness to learn about financial course. This study found the level of basic financial literacy and advance financial literacy among young generations found respectively 77 and 61. Financial literacy index counted 69, it is categorized to moderate (60-80) financial literacy index. Besides it were statistically found that previous financial courses significantly impact the financial literacy index and there is a difference between basic and advance financial literacy index among young generations. This study implies there is demanding of collaboration among government, academia, private sectors and civil society are the stakeholders to build better financial literacy to society.